How many words do children know? A corpus-based estimation of children's total vocabulary size. (July 2017) - Segbers, Jutta; Schroeder, Sascha
In this article we present a new method for estimating children's total vocabulary size based on a language corpus in German. We drew a virtual sample of different lexicon sizes from a corpus and let the virtual sample "take" a vocabulary test by comparing whether the items were included in the virtual lexicons or not. This enabled us to identify the relation between test performance and total lexicon size. We then applied this relation to the test results of a real sample of children (grades 1–8, aged 6 to 14) and young adults (aged 18 to 25) and estimated their total vocabulary sizes. Average absolute vocabulary sizes ranged from 5900 lemmas in first grade to 73, 000 for adults, with significant increases between adjacent grade levels except from first to second grade. Our analyses also allowed us to observe parts of speech and morphological development. Results thus shed light on the course of vocabulary development during primary school.